FEATURES OF LEGAL JUDGMENTS TRANSLATION FROM RUSSIAN INTO HINDI - GAZIEVA, Indira (Comparative Legilinguistics, 2017)
The translation of legal documents from Russian into Hindi is one of the most popular types of translation in the Russian Federation. The demand for translators specializing in this area is increasing. This paper will focus on the translation of legal documents from Russian into Hindi or Hindustani and on analyzing the characteristics of the translation of legal judgments. We are going to investigate the following objectives: a) to explore the stylistic characteristics of legal papers translated from Russian to Hindi; b) to determine the stylistic features of the translation of these documents at the syntactic, morphological, lexical levels. Comparing the two texts and emphasizing the constructions with steady expression in Russian and translating them into Hindi, Russian students may learn how to translate legal documents from Russian to Hindi and vice versa. They may master the translation of legal documents that subsequently may be useful to them while looking for a job in the Russian jurisdiction structures.